2015
DOI: 10.1152/ajplung.00058.2014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of translation by upstream translation initiation codons of surfactant protein A1 splice variants

Abstract: Surfactant protein A (SP-A), a molecule with roles in lung innate immunity and surfactant-related functions, is encoded by two genes in humans: SFTPA1 (SP-A1) and SFTPA2 (SP-A2). The mRNAs from these genes differ in their 5′-untranslated regions (5′-UTR) due to differential splicing. The 5′-UTR variant ACD′ is exclusively found in transcripts of SP-A1, but not in those of SP-A2. Its unique exon C contains two upstream AUG codons (uAUGs) that may affect SP-A1 translation efficiency. The first uAUG (u1) is in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Surfactant protein A (Sp-A) is a surface-coating protein involved in immune response and normal functioning of the lung [38] . The human SP-A locus comprises two functional genes called SP-A1 and SP-A2 and both of them can generate a number of 5′UTR variants through combinatorial utilization of four alternative exons [38] , [39] , [40] . At least one of these mRNA species, the Sp-A1 ACD’ isoform, contains an uORF that has been shown to dampen protein production [40] .…”
Section: The 5′utrmentioning
confidence: 99%
“…Surfactant protein A (Sp-A) is a surface-coating protein involved in immune response and normal functioning of the lung [38] . The human SP-A locus comprises two functional genes called SP-A1 and SP-A2 and both of them can generate a number of 5′UTR variants through combinatorial utilization of four alternative exons [38] , [39] , [40] . At least one of these mRNA species, the Sp-A1 ACD’ isoform, contains an uORF that has been shown to dampen protein production [40] .…”
Section: The 5′utrmentioning
confidence: 99%
“…A number of variants have been identified and characterized for each functional gene that may differentially affect regulation and/or function of alveolar cells, or the structure of surfactant films. These include variants resulting from alternative splicing events and variable translation initiation sites in the 5'-UTR (28)(29)(30), as well as isoforms with different signal peptide cleavage sites (23). Some of these have been shown to have an impact on translation efficiency and mRNA stability (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated differences between SP-A1 and SP-A2 that include both qualitative (i.e., functional, biochemical, and/or structure) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and quantitative (regulatory) changes [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. A recent study [ 60 ] examined SP-A genotype-dependent alterations in the bronchoalveolar lavage (BAL) proteome, and explored the effects of sex, infection, and ozone-induced oxidative stress on these changes.…”
Section: Introductionmentioning
confidence: 99%